THE PRESCRIPTION OF MEDICINES BY THE NURSES IN THE FAMILY HEALTH STRATEGY - Renata Borges de Vasconcelos; Janieiry Lima de Araújo (Universidade Federal do Paraná, 2013)
This qualitative study aimed to discuss the limits and possibilities of the prescription of drugs by nurses in the Family Health Strategy. 11 nurses were interviewed, and the interpretation of the information using Thematic Analysis resulted in five empirical categories. The nurses feel able to prescribe drugs in the nursing consultation; for them, the prescribing brings autonomy and professional valorization and needs caution when undertaken so as not to entail risks to the health of the service users. This practice occurs in the public health programs, but legal support from the health managers on the issue is lacking. Dialog is needed between management, the nurses, and the representative bodies of that category so that the prescription of drugs may be undertaken ethically and responsibly, with a view to public health care.